2014
DOI: 10.1371/journal.pone.0110718
|View full text |Cite
|
Sign up to set email alerts
|

HDAC6 Deacetylase Activity Is Critical for Lipopolysaccharide-Induced Activation of Macrophages

Abstract: Activated macrophages play an important role in both innate and adaptive immune responses, and aberrant activation of macrophages often leads to inflammatory and immune disorders. However, the molecular mechanisms of how macrophages are activated are not fully understood. In this study, we identify a novel role for histone deacetylse 6 (HDAC6) in lipopolysaccharide (LPS)-induced macrophage activation. Our data show that suppression of HDAC6 activity significantly restrains LPS-induced activation of macrophages… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
41
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(42 citation statements)
references
References 44 publications
(44 reference statements)
1
41
0
Order By: Relevance
“…Furthermore, HDAC6 inhibition leads to hyperacetylation of Hsp90, thereby suppressing the activity of Foxp3 + T regulatory cells 13, 14. Additionally, we have previously demonstrated that HDAC6 regulates lipopolysaccharide-induced macrophage activation in a deacetylase activity-dependent manner 15. In the present study, we have explored the role of HDAC6 in the regulation of IL-17 expression in T lymphocytes.…”
Section: Introductionmentioning
confidence: 84%
“…Furthermore, HDAC6 inhibition leads to hyperacetylation of Hsp90, thereby suppressing the activity of Foxp3 + T regulatory cells 13, 14. Additionally, we have previously demonstrated that HDAC6 regulates lipopolysaccharide-induced macrophage activation in a deacetylase activity-dependent manner 15. In the present study, we have explored the role of HDAC6 in the regulation of IL-17 expression in T lymphocytes.…”
Section: Introductionmentioning
confidence: 84%
“…HDAC6 inhibition possesses anti-tumor and anti-inflammation effects [1315]. HDAC6 has many endogenous substrates including chaperones and cytoskeletal proteins [16].…”
Section: Introductionmentioning
confidence: 99%
“…HDAC6 is predominantly present in the cytoplasm due to nuclear export signals (Bertos et al, ). HDAC6 has been implicated in the development of various human diseases, including cancers, neurological disorders, and inflammatory diseases (reviewed in Li et al, ; Vishwakarma et al, ), and functions in the regulation of pro‐ and anti‐inflammatory genes (Wang et al, ; Yan et al, ). Inhibition or knockdown of HDAC6 markedly enhances lipopolysaccharide (LPS)‐induced production of anti‐inflammatory IL‐10 by increasing p38 phosphorylation in macrophages (Wang et al, ).…”
Section: Introductionmentioning
confidence: 99%